Implementasi Kriptografi Untuk Keamanan File Text Dengan Menggunakan Metode MD5 - Ahmad Zaki Fadilla Rangkuti; Hasanul Fahmi (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2020)
Technological developments, especially in data security systems in maintaining data information security, have developed rapidly. In maintaining the security of information data, there are branches of science in its development such as cryptography. Cryptography is both the science and the art of maintaining the security of messages obtained by encoding messages to become meaningless. There are two processes in cryptography, namely encryption and decryption. To be able to secure the text file, an encryption process is carried out by changing an original text message that can be understood (plaintext) into a message that has no meaning (ciphertext) which aims to prevent the message from being known by others. Decryption is the process of returning or changing incomprehensible text code (ciphertext) into original text that can be understood (plaintext). To secure the file, the MD5 method algorithm is implemented. With that, a cryptosystem application program that is used to secure text files is created so that only certain people can process the files..